Lignolytic Enzymes Production from Selected Mushrooms - Shantaveera Swamy, H.M.; Ramalingappa, - (International Journal of Applied Sciences and Biotechnology, 2015)
In this paper, ligninase enzymes produced by selected mushrooms have been reported. We collected mushrooms from Western Ghats, most of them were edible food. Thirty samples isolated were tested using a plate assay through direct agar plate assay by using ABTS, decolourisation containing the fifteen isolates were able to decolourise the dye, indicating a lignin-degrading ability. Spectrophotometric enzyme assays from all selected isolates were carried out to examine the production of Ligninolytic enzymes (Laccase, lignin peroxidase and manganese peroxidase). Ten selected isolates produced all three kinds of enzymes tested. Lignolytic enzymes are groups of enzymes these are actively involved in bioremediation. Int J Appl Sci Biotechnol, Vol 3(2): 308-313 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12732